Inter and intraspecific interactions under experimental conditions affect behavior and feeding niche of common carp - Rahman, Mohammad Mustafizur (Faculty of Agriculture, University of Belgrade, 2018)
Among various marine and freshwater fishes, common carp (Cyprinus carpio) has perhaps attracted the most attention from humans across the globe. The high adaptive capacity along with the fast growth, early maturity and high fecundity has enabled common carp to persist and proliferate in a wide array of environments, making them widespread throughout the world (Zhou et al. 2000; Piria et al. 2016). Common carp is one of the most popular food fish in Central Asia and Europe, where it is commonly cultured in either in monoculture or polyculture ponds applying extensive or semi-intensive methods (Adamek et al. 2012; Rahman 2015). Species interaction for limited resources in the natural world leads various behavioural and feeding adaptations in species to mitigate these effects (Brannas 2008; Fox and Bellwood 2011). However, study on social and feeding behaviours of common carp through direct observation in natural environments particularly in lakes, reservoirs and rivers have largely been restricted due to high turbidity and, in consequence, low visibility. Inter and intraspecific feeding and social interactions can provide more insight on behaviour and feeding niches of common carp and co-cultured fish. To understand behavioural interactions of common carp and co-cultured fish, two separate studies were conducted in simulated ponds, in which semi-natural conditions were established. To understand the effects of various food resources on (i) feeding niche and food selectivity, and (ii) diel behavioral rhythmicity particularly grazing, swimming, resting and schooling behaviours of common carp, three treatments were compared (treatment with only plankton, treatment with plankton and benthic macroinvertebrates and treatment with plankton, benthic macroinvertebrates and artificial feed. To understand inter and intraspecific behavioral interactions, behaviours of common carp was directly observed in presence of water column feeder fish (rohu Labeo rohita). In this experiment, two densities of common carp were used with and without supplying artificial feed. In systems containing plankton and benthic macroinvertebrates, common carp mainly lived near the bottom of the system, feeding primarily on benthic macroinvertebrates. In the absence of benthic macroinvertebrates, they shifted from near the bottom to the water column where they spent majority of the time and fed principally on zooplankton. When artificial feed was available, common carp readily switched to artificial feed. However, behaviour and feeding niche of common carp were influenced by intraspecific competition, but not by the presence of other fish particularly rohu. The behaviour of rohu was greatly influenced by the presence of common carp. The results of inter and intraspecific behavioral interactions could be potentially used to further the development of common carp husbandry techniques.